Long‐term functional results after open partial horizontal laryngectomy type IIa and type IIIa: A comparison study. (11th November 2015) - Schindler, Antonio; Pizzorni, Nicole; Fantini, Marco; Crosetti, Erika; Bertolin, Andy; Rizzotto, Giuseppe; Succo, Giovanni
Abstract: Background: The purpose of this study was to compare long‐term swallowing, voice results, and quality of life (QOL) after open partial horizontal laryngectomy (OPHL) type IIa and type IIIa. Methods: Twenty‐three patients after OPHL type IIa and 18 patients after OPHL type IIIa were involved. Swallowing skills and neoglottis' motility and vibrations were videoendoscopically assessed. Aerodynamic measures, spectrogram analysis, aspiration pneumonia, body weight variations, and voice perceptual assessment were performed. Generic voice‐related and swallowing‐related QOL were assessed. Data were statistically compared using Mann–Whitney U test or Fisher exact tests, as appropriate. Results: Significant differences were found only for the residue with solids and for the intelligibility (I) parameter of the overall quality impression and intelligibility, additive and unnecessary noise, speech fluency, and presence of voiced segments scale with patients of the OPHL type IIIa group showing worse performances than the OPHL type IIa group. Conclusion: Patients who underwent OPHL type IIa and type IIIa show comparable long‐term functional outcomes. OPHL type IIIa represents a valid surgical alternative to OPHL type IIa. © 2015 Wiley Periodicals, Inc. Head Neck 38 : E1427–E1435, 2016